PENERAPAN PRINSIP-PRINSIP ETIKA DALAM PELAKSANAAN AUDIT INTERNAL MUTU: STUDI DRAMATURGI PADA UNIT KEGIATAN PELAKSANA AKADEMIK - Rijal Zul Hilmi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study was encouraged by many irregularities in ethical behavior in public organization while conducting its services to citizens, that was triggered by the lack of ethical principles application implemented in its operational activity. The aim of this research is to find out how reliable quality internal audit as a way to implement ethical principles in an organization, can really function. This research was written based on personal experience to express the complexity of interaction in the 'stages', dramaturgy was employed as methodology through conventional and Islamic ethics perspective. To analyse through ethics profession applied, this research will focus on analysis impressions management conducted by the actors. The results of this research indicated that the audit internal quality was able to apply the principles of professional ethics even though there were still insufficient in some aspect, as well as lack of conformity to ethical, conduct to the Islamic perspective. Following the existence of these deficiencies, this research presented an idea to further enhance awareness of soul and mind to either auditor and auditee in conducty the quality internal audit. Keywords: Application of Ethical Principles, Internal Audit Quality, Dramaturgy, Code of Conduct Conventional, Islamic Ethics, Impressions Management